KEJUJURAN PELAPORAN PAJAK: EFEK PERSEPSI PENURUNAN TARIF PAJAK DAN PEMAHAMAN SISTEM PEMUNGUTAN PERPAJAKAN - Widayanti, Novita Christy; Damayanti, Theresia Woro (APSSAI ACCOUNTING REVIEW, 2022)
This study aims to determine whether perceptions of reducing MSME tax rates and understanding the tax collection system affect the honesty of reporting. This research uses primary data obtained directly from MSME in Salatiga using a vignette experiment embedded in a survey questionnaire and an accidental sampling method. The data analysis technique used is multiple linear regression analysis. The results showed that partially the perception of a reduction in the MSME tax rate did not affect the honesty of reporting. Meanwhile, understanding the tax collection system positively affects the honesty of reporting. Although partially, the perception of a reduction in the MSME tax rate has no effect, simultaneously, the perception of a reduction in MSME tax rates and an understanding of the tax collection system positively affect the honesty of reporting.